EFEKTIVITAS PENGGUANAAN QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS DI SMP TELKOM MAKASSAR - Wardaningsih; Falihin, Dalilul; Ibrahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using Quizizz as a learning medium in increasing student learning motivation in social studies at Telkom Makassar Junior High School. This study used a quantitative method using a Quasi-Experimental method using a Nonequivalent Control Group Design. The population in this study were students of Telkom Makassar Junior High School, with a sample of 62 respondents divided into an experimental class of 31 students and a control class of 31 students. Data collection used a learning motivation questionnaire that had been tested for validity and reliability. Data analysis used descriptive statistics, normality tests, homogeneity tests, Independent Sample T-Tests, and N-Gain Score tests. The results of the study showed that: 1) There was a significant difference in the level of student learning motivation between the class using Quizizz learning media and the class using conventional methods, where the experimental class's achievements were descriptively superior. This change in motivation was reflected in the fulfillment of eight indicators of student learning motivation including the duration of activities, frequency of activities, level of qualification of results, and direction of attitude towards activity targets. 2) The use of Quizizz learning media was proven effective in increasing student learning motivation based on the results of the N-Gain Score analysis of the experimental class which was in a higher improvement category compared to the control class. This effectiveness was driven by the fulfillment of five indicators of interactive media, namely cognitive content, information presentation, ease of navigation, aesthetics, and the overall function of the Quizizz gamification feature.